ANALYSIS OF THE POTENTIAL ATTRACTION OF ECO-KARST TOURISM OF MARON RIVER, DERSONO VILLAGE, PRINGKUKU DISTRICT PACITAN REGENCY - Pipit Wijayanti; Muhammad Zaki Zamani (GeoEco, 2022)
Tourism is one of the ways for residents at the village to gain income and aslo a contributor to the national economy. The tourism that is found in every village nowadays favors the potential of the surrounding nature. Pacitan Regency is known to have tourism potential related to the advantages of its karst landscape. Pacitan also got the nickname "1000 Goa" because there are many karst caves found there. Villages in Pacitan Regency have developed a lot of eco-karst tourism. Dersono Village is a village located in Pringkuku District, Pacitan Regency. There is one leading eco-karst tourism in the village that is currently being managed, namely the Maron River. Although it has similarities with other tourism in Pacitan Regency, which is the same theme of eco-karst, however Maron River certainly has its own attraction which made tourists who come to Pacitan Regency decided to visit the Maron River This study aims to analyze the potential for tourism attraction of Maron River based on the 4A tourism components. The method used in this study is descriptive research with data collection through observation and interviews. Based on the results of the study, the study found that the tourism attraction of Maron River based on 4A has met the parameters. However, it still needs to be developed so that the number of tourist visits continues to increase and can be expanded with new eco-karst attractions.